2009
DOI: 10.1590/s1413-35552009005000045
|View full text |Cite
|
Sign up to set email alerts
|

Gluteus maximus and semitendinosus activation during active prone hip extension exercises

Abstract: Background: Gluteus maximus strengthening exercises are employed in clinical practice as options for the treatment of low back and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…These procedures allowed comparisons between different individuals and studies and reduced the inter-subject coefficients of variation 24 . Normalization by the maximum voluntary contractions was not chosen, as previously employed 25 , because this procedure could not have been trustworthy for individuals with LBP, as they would not be able to perform maximum contractions due to the pain [26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These procedures allowed comparisons between different individuals and studies and reduced the inter-subject coefficients of variation 24 . Normalization by the maximum voluntary contractions was not chosen, as previously employed 25 , because this procedure could not have been trustworthy for individuals with LBP, as they would not be able to perform maximum contractions due to the pain [26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Seven complained of pain in the direction of extension, three in the direction of flexion, seven in both directions, and two did not show any specific patterns. Clinically, these individuals had a score of 28.58 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Figure 2 shows the muscular latencies of all investigated muscles for the asymptomatic (2a) and LBP (2b) individuals. For the asymptomatic group, the muscular activation patterns were initiated by the semitendinosus, followed by the ipsilateral erector spinae, contralateral erector spinae and finished by the gluteus maximus.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…A systematic review that investigated exercise therapy for improving muscle activity onset times concluded that training involving selective muscle activation improves muscle activity onset times 8 ) , suggesting that training involving selective GM activation might improve GM activity patterns in people with low back pain. One exercise for suppressing HAM activity and activating GM that is often used clinically is prone hip extension with knee flexion (PHEKF) 9 ) . Kang et al 10 ) and Sakamoto et al 9 ) investigated the impact of muscle activity during PHEKF exercise using hip joint abduction and external rotation to discover a method for activating the GM.…”
Section: Introductionmentioning
confidence: 99%
“…For pelvic stability and safe and effective movement of the lower limbs, a GM strengthening exercise has been applied for rehabilitation training. The GM strengthening exercise, prone hip extension with knee flexion (PHEKF) exercise, is a well-known, effective method for activation of the GM muscle during lower limb extension [11]. Recent research on application of the PHEKF exercise has used electromyography (EMG) and measurement of the angle of the leg to assess the activation of the GM [12].…”
Section: Introductionmentioning
confidence: 99%